Optimal Placement of Meat Bone Meal Pellets to Spring Oats - Delin, Sofia; Engström, Lena; Lundkvist, Anneli (Frontiers in Sustainable Food Systems, 2018)
New technology makes it possible to apply organic fertilizers with higher precision, and organic producers want to know how to exploit these new possibilities to make their production more efficient. This study investigated the effect of band application (in different positions) of pelleted organic fertilizer, compared with broadcasting, on grain yield and weed density in spring oats (Avena sativa L.). Six microplot field experiments were carried out on silty clay and sandy loam in Sweden during the growing season of 2014-2016. In oats seeded at 25 cm row spacing, pelleted meat bone meal was band-applied at one of three distances from the crop row (0, 4, and 12.5 cm) and at two or three incorporation depths (1 and 4 cm on silty clay and 1, 4, and 6 cm on loamy sand). These treatments were compared with broadcast spreading, mineral nitrogen fertilizer, and an unfertilized control. On both soil types, fertilizer placement 4 cm from the crop and 4-6 cm incorporation depth gave the highest yield and crop nitrogen uptake. Yield in this treatment was 800 kg ha-1 higher on clay soil and 1100 kg ha-1 higher on sandy loam compared with the same organic fertilizer applied by broadcasting, an 80-150% yield increase. On the sandy loam, distance from the crop row had a more significant effect on grain yield (p<0.001) than soil incorporation depth (p=0.07). On the silty clay, crop yield was significantly influenced by incorporation depth (p=0.003) and distance from the crop row (p=0.04). In five experiments, mineral N fertilizer equivalent (MFE) increased from on average 63% with broadcasting to 85% with placement 4 cm from the crop row and 4 cm incorporation depth. Weed biomass was significantly affected by fertilizer placement on the clay soil, with higher weed biomass with deeper incorporation (p=0.045) and greater distance from the crop row (p=0.049). On the sandy loam, there was a tendency for larger weed plants at greater distance from the crop row (p=0.13) except when seeds and pellets were placed together, which gave the highest weed weight, probably due to lower competition from the crop in this treatment.